Production process of moisture-proof and salt-spray-corrosion-resistant repair adhesive

By mixing epoxy resin, silane coupling agent, inorganic filler and glass fiber mesh and heating and solidifying, a fluid glue is formed, which solves the problem of salt spray corrosion and pollution of power system insulation parts, and achieves efficient and economical insulation repair effect.

CN119331554APending Publication Date: 2025-01-21衡诚能源科技(上海)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411557984.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When solving the salt spray corrosion and pollution problems of insulating parts of power system, the prior art has the disadvantages of high costs, difficult construction and limited repair results.

Method used

A combination of epoxy resin, silane coupling agent, inorganic filler and glass fiber mesh is used, mixed in a reactor and cured by heating to form a fluid glue, which is cured under heating conditions to form a dense insulating protective layer.

Benefits of technology

The insulation and repair glue of rapid solidification has been realized, and it has good insulation performance. It can effectively prevent salt fog corrosion and pollution, and reduce the cost and difficulty of construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331554A_ABST
    Figure CN119331554A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of power cables, in particular to a production process of a moisture and salt spray corrosion resistant repair adhesive, which comprises the following steps: (1) mixing epoxy resin, a silane coupling agent, an inorganic filler and a doped fragment-shaped glass fiber mesh in a reaction kettle, and vacuumizing the reaction kettle before mixing; (2) adding a curing agent into the reaction kettle, and fully stirring to enable all the components to fully react; (3) adding a solvent into the reaction kettle, adjusting the viscosity of the coating, and mixing the materials in the reaction kettle into fluid glue; (4) transferring the stirred and mixed fluid glue into another reaction kettle, adding a cross-linking agent into the reaction kettle, uniformly stirring, and then carrying out vacuumizing treatment again so as to remove gas impurities generated in the reaction process; (5) uniformly coating the prepared coating on the surface of the to-be-repaired insulating part; (6) curing under a heating condition to form a compact insulating protection layer; therefore, the high-strength corrosion-resistant easy-to-use repair adhesive is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of power cables, and in particular to an insulation repair adhesive. Background Art

[0002] In the existing power system maintenance, the salt spray corrosion and pollution of insulation parts has always been a difficult problem that is difficult to completely solve. Due to environmental factors and material aging, conductive paths are easily formed on the surface of insulation parts, resulting in reduced insulation performance and even insulation breakdown failure.

[0003] Traditional repair methods, such as replacing insulation parts or using conventional APG processes, power ceramics, DMC and SMC die-cast insulation parts processes, can solve insulation problems to a certain extent, but these methods have the disadvantages of high cost, difficult construction and limited repair effect. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification and the title of the invention of this application to avoid blurring the purpose of this section, the abstract of the specification and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems existing in the prior art, the present invention is proposed.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] Step (1) mixing epoxy resin, silane coupling agent, inorganic filler, and glass fiber mesh in a doped state in a reactor, and evacuating the reactor before mixing;

[0008] The silane coupling agent includes γ-aminopropyltriethoxysilane, γ-vinyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane;

[0009] In terms of weight percentage, epoxy resin 50%-58%, silane coupling agent 0.7%-0.8%, inorganic filler 22%-28%;

[0010] The glass fiber mesh comprises a mesh body and expanded glass fibers;

[0011] The net body is woven with warp and weft;

[0012] Both the warp and weft threads are made of fiberglass;

[0013] The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers;

[0014] Step (2) adding a curing agent to the reaction kettle and stirring sufficiently to allow the components to react sufficiently, wherein the curing agent is 0.02% to 0.03% by weight;

[0015] Step (3) adding solvent to the reaction kettle to adjust the viscosity of the coating, in terms of weight percentage, the solvent is 1%-1.5%, and the materials in the reaction kettle are mixed to form a fluid glue;

[0016] Step (4) transferring the stirred and mixed fluid glue to another reaction kettle, adding a crosslinking agent thereto, stirring evenly, and then performing a vacuum treatment again to remove gas impurities generated during the reaction;

[0017] In terms of weight percentage, the cross-linking agent is 0.7%-1%;

[0018] Step (5) uniformly coating the prepared coating on the surface of the insulating part to be repaired;

[0019] Step (6) solidifies under heating conditions to form a dense insulating protective layer.

[0020] The above design, through the coordinated use of curing agent and solvent, enables the fluid glue to maintain fluid properties when mixed with curing agent. When in use, the sprayed fluid glue is quickly cured after the solvent evaporates quickly to form a fast-curing repair glue. The inorganic filler and epoxy resin have good insulation properties after curing to ensure the insulation properties of the repair glue. The silane coupling agent adopts one or more of γ-aminopropyltriethoxysilane (KH330), γ-vinyltriethoxysilane (KH550), and γ-glycidyloxypropyltrimethoxysilane (KH570); it has good water resistance and chemical resistance, can effectively improve the bonding effect between organic and inorganic materials, can improve the moisture and salt spray corrosion resistance of the repair glue production process after curing, and can resist salt spray corrosion and pollution problems.

[0021] In step (1), epoxy resin, silane coupling agent, inorganic filler in a specific proportion and glass fiber mesh in a doped form are uniformly mixed in a reactor, and the reactor is vacuumed before mixing to ensure the purity of the reaction environment. Subsequently, the base material is heated to a suitable reaction temperature. While heating, stirring is continued to ensure that the base material is evenly heated and fully mixed. Through this series of operations, impurities in the base material can be effectively removed, the purity and quality of the product can be improved, and the corrosion resistance of the fluid glue can be improved.

[0022] Preferably, in the glass fiber mesh, the diameter of the glass fibers is 6.2-9.5 μm; the area of ​​the mesh is 0.55-2.5 mm 2 , mesh area is 0.01-0.18mm 2; The length of the expanded glass fiber is 0.45-1.95mm; in terms of volume, there are 3-6 glass fiber meshes per cubic centimeter.

[0023] The 6.2-9.5μm glass fiber woven mesh has good softness and certain toughness. The area of ​​the mesh is 0.55-2.5mm 2 The fragmented glass fiber mesh is not easy to be tangled into a ball after being mixed into the polymer moisture-proof plugging glue as a filler. The mesh area is 0.01-0.18mm 2 , allowing the silicone base material to pass through the mesh and combine more strongly with the glass fiber mesh. Improve the strength of the fluid glue after curing. The diameter of the glass fiber is 6.2-9.5μm, and there are 3-6 glass fiber meshes per cubic centimeter. While ensuring the number of fiber meshes is moderate, ensure that the expanded glass fibers are intertwined as much as possible to form a three-dimensional mesh structure, improve the overall strength, and facilitate the magnetic field to produce a better effect.

[0024] Preferably, the inorganic filler includes aluminum oxide, silicon oxide, hollow glass microspheres and boron nitride. The inorganic filler also includes a 1:1 mixture of aluminum hydroxide and magnesium oxide; these materials have good insulation properties to improve the insulation properties of the insulation repair adhesive after curing. The particle size of the hollow glass microspheres is at the submicron to micron level, making it easy to mix with other materials to form a composite material. Due to the hollow structure, it has good insulation properties and a relatively low density.

[0025] Preferably, in step (2), the curing agent is added under negative pressure and stirred continuously until dissolved to reduce the generation of bubbles; a two-stage stirring method is adopted, firstly stirring at a low speed to evenly disperse the filler, and then stirring at a high speed to promote the full reaction of the curing agent and the resin; the curing agent includes a polyamide resin curing agent, a polyamide-amine type curing agent and a bio-based curing agent; these curing agents have the characteristics of fast curing of epoxy resin, and reducing the generation of bubbles can further improve the resistance of the cured fluid adhesive to moisture and salt spray corrosion, and the full reaction of the curing agent and the resin improves the strength of the fluid adhesive after curing.

[0026] Preferably, the solvent includes a water-based solvent, a 1:1 mixed solvent of xylene and ethyl acetate, a dimethylformamide solvent and a butyl acetate solvent; since the main component of the water-based solvent is water, the VOC (volatile organic compound) emission of the water-based solvent is low and meets environmental protection requirements; the 1:1 mixed solvent of xylene and ethyl acetate, the dimethylformamide solvent and the butyl acetate solvent have strong dissolving ability and are easy to evaporate, but have certain toxicity and irritation. When using, make sure to wear appropriate protective equipment and operate in a well-ventilated environment.

[0027] Preferably, when the fluid glue in another reactor is stirred in step (4), a protective gas is poured into the other reactor. After the protective gas is poured in, stirring is continued so that the protective gas and the fluid glue are fully mixed. This prevents the product from being affected by oxygen and moisture during storage and use. The pouring of the protective gas can effectively isolate harmful gases in the external environment, ensure the stability of the product and extend its shelf life. After the protective gas is poured in, stirring is continued so that the protective gas and the base material are fully mixed to achieve a uniform distribution effect, thereby reducing the influence of the fluid glue on the humid or salt spray environment and improving the ability of the cured fluid glue to resist moisture and salt spray corrosion.

[0028] Preferably, an electromagnetic induction heating furnace is provided for heating the fluid glue in the reactor; the electromagnetic induction heating furnace has an automatic temperature control system, and the automatic temperature control system has a microprocessor system; the soft magnetic powder on the glass fiber net has soft magnetic properties, and can introduce a magnetic field into the depth of the fluid glue, forming a relatively uniform magnetic field distributed in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated; a temperature sensor is also provided in the reactor, and the temperature sensor is connected to the microprocessor system; the electromagnetic induction heating furnace is turned on to high power operation when the temperature in the reactor is below 80 degrees Celsius; the electromagnetic induction heating furnace is turned on to medium power operation when the temperature in the reactor is above 80 degrees Celsius, and the medium power is 50%-70% of the high power value; the electromagnetic induction heating furnace is turned on to low power operation when the temperature in the reactor is above 150 degrees Celsius, and the low power is 20%-30% of the high power value. Because the specially designed glass fiber net of the present invention is used, the induction heat can be more evenly distributed inside the fluid glue, avoiding the problem of local flash evaporation caused by local overheating. At the same time, stage-type heating power control is adopted according to temperature setting, which ensures heating efficiency while avoiding flash evaporation.

[0029] Preferably, in step (1), the production method of the glass fiber mesh comprises the following steps: (1) when drawing the glass fiber as one of the warp and weft threads, soft magnetic powder dust is sprayed onto the molten glass fiber through a nozzle in a molten state, and the soft magnetic powder dust is bonded thereto, and the particle size of the soft magnetic powder is 0.05-0.20 μm; and (2) when drawing the other glass fiber as the warp and weft threads, soft magnetic powder dust is sprayed onto the molten glass fiber through a nozzle in a molten state, and graphite powder is bonded thereto, and the particles of the graphite powder are 6-10 μm.

[0030] Glass fiber is bonded with soft magnetic powder. Soft magnetic powder has soft magnetic properties and can introduce magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated. 50-200nm soft magnetic powder can form a more uniform dispersion in the glass fiber and enhance the magnetic properties. At this fine particle size, soft magnetic powder can improve the electromagnetic properties of the material, reduce losses, and provide better interaction and adhesion. 6-10μm graphite dust is relatively small and easy to disperse. After the fluid glue is cured, it is easy to disconnect the electrical contact to ensure the insulation performance of the insulation repair glue.

[0031] The crosslinking agent is either pentanoic anhydride or phthalic anhydride. The chemical structure of pentanoic anhydride gives it good heat resistance and chemical resistance, making it suitable for high-performance applications; the relatively slow curing rate of phthalic anhydride allows for better control of fluidity, avoiding bubbles and defects.

[0032] Preferably, in step (6), the fluid glue is assisted in curing by an auxiliary curing device, the auxiliary curing device includes an electromagnet, an oscillating circuit is connected to the electromagnet to generate a magnetic field with periodic direction changes, and the electromagnet is close to the fluid glue coating position; the soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the fluid glue, thereby ensuring the corrosion resistance of the fluid glue; while vibrating, it also promotes the tightness of the glass fiber and the fluid glue, and the graphite powder and the fluid glue are evenly mixed on the glass fiber mesh to form a conductive fluid.

[0033] In a further step (6), the auxiliary curing equipment includes a microwave heating device, which generates an alternating magnetic field, and the fluid glue is heated and cured by the microwave heating device; the soft magnetic powder on the glass fiber has soft magnetic properties, which can introduce the magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated.

[0034] In step (6), auxiliary curing is performed by an auxiliary curing device. The electromagnet is close to the fluid glue coating position. The soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the fluid glue; while vibrating, it also promotes the tightness of the glass fiber and the fluid glue. The graphite powder and the fluid glue are evenly mixed on the glass fiber net to form a conductive fluid. The microwave heating device generates an alternating magnetic field to heat the conductive fluid. Under the heating condition, the crosslinking agent can react with the functional groups in the epoxy resin through a thermal reaction to form a crosslinking structure, quickly cure the epoxy resin, and thus form a stronger insulating layer. The cured structure can reduce the electrical contact between the graphite powder. Inorganic fillers with stronger insulation properties (such as aluminum oxide, silicon oxide, hollow glass microspheres, boron nitride or a 1:1 mixture of aluminum hydroxide and magnesium oxide) added to the epoxy resin can improve the insulation performance of the insulating repair glue after curing. These materials can be used together with graphite powder to cut off the electrical contact of the graphite powder in the fluid after the fluid glue is cured, so that the fluid glue maintains the insulating properties after curing, and the volume resistivity can reach 10^ 13 Ω·cm or more, and the dielectric strength can reach over 20kV / mm.

[0035] The result is a corrosion-resistant, high-strength, easy-to-use repair adhesive that is resistant to moisture and salt spray corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0037] Figure 1 A schematic diagram of the structural principle of a glass fiber mesh with smart grid access function according to an embodiment of the present invention;

[0038] Figure 2 A microscopic display of a glass fiber mesh with non-shortened expanded glass fibers having a smart grid access function as described in an embodiment of the present invention. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more understandable, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.

[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0041] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0042] Furthermore, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in less than one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0043] refer to Figure 1 and Figure 2 , production process of repair glue that prevents moisture and salt spray corrosion.

[0044] Step (1) mixing epoxy resin, silane coupling agent, inorganic filler, and glass fiber mesh 1 in a doped state in a reactor, and evacuating the reactor before mixing;

[0045] The silane coupling agent includes γ-aminopropyltriethoxysilane, γ-vinyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane;

[0046] In terms of weight percentage, epoxy resin 50%-58%, silane coupling agent 0.7%-0.8%, inorganic filler 22%-28%;

[0047] The glass fiber mesh 1 includes a mesh body 11 and expanded glass fibers 12;

[0048] The net body 11 is woven with warp and weft;

[0049] Both the warp and weft threads are made of fiberglass;

[0050] The lengths of at least part of the warp threads and at least part of the weft threads are both beyond the mesh body 11, forming extended glass fibers 12;

[0051] Step (2) adding a curing agent to the reaction kettle and stirring sufficiently to allow the components to react sufficiently, wherein the curing agent is 0.02% to 0.03% by weight;

[0052] Step (3) adding solvent to the reaction kettle to adjust the viscosity of the coating, in terms of weight percentage, the solvent is 1%-1.5%, and the materials in the reaction kettle are mixed to form a fluid glue;

[0053] Step (4) transferring the stirred and mixed fluid glue to another reaction kettle, adding a crosslinking agent thereto, stirring evenly, and then performing a vacuum treatment again to remove gas impurities generated during the reaction;

[0054] In terms of weight percentage, the cross-linking agent is 0.7%-1%;

[0055] Step (5) uniformly coating the prepared coating on the surface of the insulating part to be repaired;

[0056] Step (6) solidifies under heating conditions to form a dense insulating protective layer.

[0057] The above design, through the coordinated use of curing agent and solvent, enables the fluid glue to maintain fluid properties when mixed with curing agent. When in use, the sprayed fluid glue is quickly cured after the solvent evaporates quickly to form a fast-curing repair glue. The inorganic filler and epoxy resin have good insulation properties after curing to ensure the insulation properties of the repair glue. The silane coupling agent adopts one or more of γ-aminopropyltriethoxysilane (KH330), γ-vinyltriethoxysilane (KH550), and γ-glycidyloxypropyltrimethoxysilane (KH570); it has good water resistance and chemical resistance, can effectively improve the bonding effect between organic and inorganic materials, can improve the moisture and salt spray corrosion resistance of the repair glue production process after curing, and can resist salt spray corrosion and pollution problems.

[0058] In step (1), epoxy resin, silane coupling agent, inorganic filler in a specific proportion, and glass fiber mesh 1 in a doped form are uniformly mixed in a reactor, and the reactor is vacuumed before mixing to ensure the purity of the reaction environment. Subsequently, the base material is heated to a suitable reaction temperature. While heating, stirring is continued to ensure that the base material is evenly heated and fully mixed. Through this series of operations, impurities in the base material can be effectively removed, the purity and quality of the product can be improved, and the corrosion resistance of the fluid glue can be improved.

[0059] Preferably, in the glass fiber mesh 1, the diameter of the glass fibers is 6.2-9.5 μm; the area of ​​the mesh body 11 is 0.55-2.5 mm 2 , mesh area is 0.01-0.18mm 2 The length of the extended glass fiber 12 is 0.45-1.95 mm; in terms of volume, there are 3-6 glass fiber meshes 1 per cubic centimeter.

[0060] The 6.2-9.5μm glass fiber woven mesh has good softness and certain toughness. The area of ​​the mesh body 11 is 0.55-2.5mm 2 The formed fragmented glass fiber mesh 1 is not easy to be tangled into a ball after being mixed into the polymer moisture-proof plugging glue as a filler. The mesh area is 0.01-0.18mm 2 , allowing the silicone base material to pass through the mesh and to be more strongly combined with the glass fiber mesh 1. Improving the strength of the fluid glue after curing. The diameter of the glass fiber is 6.2-9.5μm, and there are 3-6 glass fiber meshes 1 per cubic centimeter. Under the condition of ensuring a moderate number of fiber meshes, the expanded glass fibers 12 are ensured to be interlaced as much as possible to form a three-dimensional mesh structure, improve the overall strength, and facilitate the better effect of the magnetic field generation effect.

[0061] Preferably, the inorganic filler includes aluminum oxide, silicon oxide, hollow glass microspheres and boron nitride. The inorganic filler also includes a 1:1 mixture of aluminum hydroxide and magnesium oxide; these materials have good insulation properties to improve the insulation properties of the insulation repair adhesive after curing. The particle size of the hollow glass microspheres is at the submicron to micron level, making it easy to mix with other materials to form a composite material. Due to the hollow structure, it has good insulation properties and a relatively low density.

[0062] Preferably, in step (2), the curing agent is added under negative pressure and stirred continuously until dissolved to reduce the generation of bubbles; a two-stage stirring method is adopted, firstly stirring at a low speed to evenly disperse the filler, and then stirring at a high speed to promote the full reaction of the curing agent and the resin; the curing agent includes a polyamide resin curing agent, a polyamide-amine type curing agent and a bio-based curing agent; these curing agents have the characteristics of fast curing of epoxy resin, and reducing the generation of bubbles can further improve the resistance of the cured fluid adhesive to moisture and salt spray corrosion, and the full reaction of the curing agent and the resin improves the strength of the fluid adhesive after curing.

[0063] Preferably, the solvent includes a water-based solvent, a 1:1 mixed solvent of xylene and ethyl acetate, a dimethylformamide solvent and a butyl acetate solvent; since the main component of the water-based solvent is water, the VOC (volatile organic compound) emission of the water-based solvent is low and meets environmental protection requirements; the 1:1 mixed solvent of xylene and ethyl acetate, the dimethylformamide solvent and the butyl acetate solvent have strong dissolving ability and are easy to evaporate, but have certain toxicity and irritation. When using, make sure to wear appropriate protective equipment and operate in a well-ventilated environment.

[0064] Preferably, when the fluid glue in another reactor is stirred in step (4), a protective gas is poured into the other reactor. After the protective gas is poured in, stirring is continued so that the protective gas and the fluid glue are fully mixed. This prevents the product from being affected by oxygen and moisture during storage and use. The pouring of the protective gas can effectively isolate harmful gases in the external environment, ensure the stability of the product and extend its shelf life. After the protective gas is poured in, stirring is continued so that the protective gas and the base material are fully mixed to achieve a uniform distribution effect, thereby reducing the influence of the fluid glue on the humid or salt spray environment and improving the ability of the cured fluid glue to resist moisture and salt spray corrosion.

[0065] Preferably, an electromagnetic induction heating furnace is provided for heating the fluid glue in the reactor; the electromagnetic induction heating furnace has an automatic temperature control system, and the automatic temperature control system has a microprocessor system; the soft magnetic powder on the glass fiber mesh 1 has soft magnetic properties, and can introduce a magnetic field into the depth of the fluid glue, forming a relatively uniform magnetic field distributed in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated; a temperature sensor is also provided in the reactor, and the temperature sensor is connected to the microprocessor system; the electromagnetic induction heating furnace is turned on to high power operation when the temperature in the reactor is below 80 degrees Celsius; the electromagnetic induction heating furnace is turned on to medium power operation when the temperature in the reactor is above 80 degrees Celsius, and the medium power is 50%-70% of the high power value; the electromagnetic induction heating furnace is turned on to low power operation when the temperature in the reactor is above 150 degrees Celsius, and the low power is 20%-30% of the high power value. Because the specially designed glass fiber mesh 1 of the present invention is used, the induction heat can be more evenly distributed inside the fluid glue, avoiding the problem of local flash evaporation caused by local overheating. At the same time, stage-type heating power control is adopted according to temperature setting, which ensures heating efficiency while avoiding flash evaporation.

[0066] Preferably, in step (1), the production method of the glass fiber mesh 1 comprises the following steps: (1) when drawing the glass fiber as one of the warp and weft threads, soft magnetic powder dust is sprayed onto the molten glass fiber through a nozzle in a molten state, and the soft magnetic powder dust is bonded thereto, and the particle size of the soft magnetic powder is 0.05-0.20 μm; and (2) when drawing the glass fiber as the other of the warp and weft threads, soft magnetic powder dust is sprayed onto the molten glass fiber through a nozzle in a molten state, and graphite powder is bonded thereto, and the particles of the graphite powder are 6-10 μm.

[0067] Glass fiber is bonded with soft magnetic powder. Soft magnetic powder has soft magnetic properties and can introduce magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated. 50-200nm soft magnetic powder can form a more uniform dispersion in the glass fiber and enhance the magnetic properties. At this fine particle size, soft magnetic powder can improve the electromagnetic properties of the material, reduce losses, and provide better interaction and adhesion. 6-10μm graphite dust is relatively small and easy to disperse. After the fluid glue is cured, it is easy to disconnect the electrical contact to ensure the insulation performance of the insulation repair glue.

[0068] The crosslinking agent is either pentanoic anhydride or phthalic anhydride. The chemical structure of pentanoic anhydride gives it good heat resistance and chemical resistance, making it suitable for high-performance applications; the relatively slow curing rate of phthalic anhydride allows for better control of fluidity, avoiding bubbles and defects.

[0069] Preferably, in step (6), the fluid glue is assisted in curing by an auxiliary curing device, the auxiliary curing device includes an electromagnet, an oscillating circuit is connected to the electromagnet to generate a magnetic field with periodic direction changes, and the electromagnet is close to the fluid glue coating position; the soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the fluid glue, thereby ensuring the corrosion resistance of the fluid glue; while vibrating, it also promotes the tightness of the glass fiber and the fluid glue, and the graphite powder and the fluid glue are evenly mixed on the glass fiber mesh 1 to form a conductive fluid.

[0070] In a further step (6), the auxiliary curing equipment includes a microwave heating device, which generates an alternating magnetic field, and the fluid glue is heated and cured by the microwave heating device; the soft magnetic powder on the glass fiber has soft magnetic properties, which can introduce the magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated.

[0071] In step (6), auxiliary curing is performed by an auxiliary curing device. The electromagnet is close to the fluid glue coating position. The soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the fluid glue; while vibrating, it also promotes the tightness of the glass fiber and the fluid glue. The glass fiber mesh 1 has graphite powder and the fluid glue uniformly mixed to form a conductive fluid. The microwave heating device generates an alternating magnetic field to heat the conductive fluid. Under the heating condition, the crosslinking agent can react with the functional groups in the epoxy resin through a thermal reaction to form a crosslinking structure, quickly cure the epoxy resin, and thus form a more solid insulating layer. The cured structure can reduce the electrical contact between the graphite powder. Inorganic fillers with stronger insulation properties (such as aluminum oxide, silicon oxide, hollow glass microspheres, boron nitride or a 1:1 mixture of aluminum hydroxide and magnesium oxide) added to the epoxy resin can improve the insulation performance of the insulating repair glue after curing. These materials can be used together with graphite powder to cut off the electrical contact of the graphite powder in the fluid after the fluid glue is cured, so that the fluid glue maintains the insulating properties after curing, and the volume resistivity can reach 10^ 13 Ω·cm or more, and the dielectric strength can reach over 20kV / mm.

[0072] Embodiment 1:

[0073] Weigh 100 parts of environmentally friendly epoxy resin, 1 part of non-volatile silane coupling agent KH550, 50 parts of environmentally friendly alumina inorganic filler, 5 parts of low-VOC polyamide resin curing agent, and a water-based solvent doped with 1 glass fiber mesh.

[0074] Mixing and stirring: Add epoxy resin, silane coupling agent and inorganic filler into the reaction kettle, control the temperature between room temperature and 40°C, stir at a moderate speed to ensure that the components are initially mixed evenly.

[0075] Adding curing agent and solvent: In the reaction kettle, slowly add the polyamide resin curing agent under negative pressure, continue stirring until it is completely dissolved, and avoid the generation of bubbles. Then, add a water-based solvent to adjust the viscosity.

[0076] During the stirring process, the electromagnetic induction heating furnace uses electromagnetic induction heating of the glass fiber mesh to make the induction heat more evenly distributed inside the fluid glue, avoiding the problem of local overheating and local flash evaporation. At the same time, the staged heating power control is set according to the temperature, which ensures the heating efficiency and avoids flash evaporation under the premise of avoiding flash evaporation.

[0077] Coating and curing: The prepared repair glue is evenly coated on the surface of the insulating part to be repaired, and a strong magnetic field distribution is formed around the interwoven graphite powder bonded to the glass fiber through a microwave heating device, thereby generating induction heat and evenly heating the fluid glue.

[0078] The water-based solvent evaporates quickly and the curing agent reacts with the epoxy resin, resulting in a fast cure.

[0079] Water-based solvents reduce VOC emissions, minimizing the impact on the environment and reducing the impact on the environment.

[0080] Embodiment 2:

[0081] 80 parts of epoxy resin, 0.8 parts of silane coupling agent KH570, 60 parts of silica inorganic filler, 6 parts of modified polyamide curing agent, 15 parts of butyl acetate solvent and 1 part of glass fiber mesh are used.

[0082] Mixing and stirring: Add epoxy resin, silane coupling agent and inorganic filler into the reaction kettle, control the temperature between room temperature and 40°C, stir at a moderate speed to ensure that the components are initially mixed evenly.

[0083] Adding curing agent and solvent: In the reaction kettle, slowly add the modified polyamide curing agent under negative pressure, continue stirring until it is completely dissolved, and avoid the generation of bubbles. Then, add butyl acetate to adjust the viscosity.

[0084] During the stirring process, the electromagnetic induction heating furnace uses electromagnetic induction heating of the glass fiber mesh to make the induction heat more evenly distributed inside the fluid glue, avoiding the problem of local overheating and local flash evaporation. At the same time, the staged heating power control is set according to the temperature, which ensures the heating efficiency and avoids flash evaporation under the premise of avoiding flash evaporation.

[0085] Coating and curing: The prepared repair glue is evenly coated on the surface of the insulating part to be repaired. A strong magnetic field distribution is formed around the glass fiber by a microwave heating device, which generates induction heat and evenly heats the fluid glue. The butyl acetate solvent evaporates quickly, and the curing agent reacts with the epoxy resin, thereby achieving rapid curing of the fluid glue.

[0086] Butyl acetate is more volatile, but its odor is relatively good and is suitable for indoor applications. However, proper ventilation and personal protection should still be observed.

[0087] Embodiment 3:

[0088] 90 parts of epoxy resin, 1.5 parts of a mixture of silane coupling agents KH330 and KH550 (1:1 ratio), 30 parts of hollow glass microsphere functional filler, 4 parts of polyamide-amine type curing agent, 25 parts of dimethylformamide solvent, and 1 glass fiber mesh were used.

[0089] Mixing and stirring: Add epoxy resin, silane coupling agent and inorganic filler into the reaction kettle, control the temperature between room temperature and 40°C, stir at a moderate speed to ensure that the components are initially mixed evenly.

[0090] Adding curing agent and solvent: In the reaction kettle, slowly add polyamide-amine curing agent under negative pressure, continue stirring until completely dissolved, and avoid the generation of bubbles. Then, add dimethylformamide solvent to adjust the viscosity.

[0091] During the stirring process, the electromagnetic induction heating furnace uses electromagnetic induction heating of the glass fiber mesh to make the induction heat more evenly distributed inside the fluid glue, avoiding the problem of local overheating and local flash evaporation. At the same time, the staged heating power control is set according to the temperature, which ensures the heating efficiency and avoids flash evaporation under the premise of avoiding flash evaporation.

[0092] The treated fluid glue is transferred to another reaction kettle, a cross-linking agent is added thereto, and after being stirred evenly, vacuum treatment is performed again to remove gas impurities that may be generated during the reaction.

[0093] Coating and curing: The prepared repair glue is evenly coated on the surface of the insulating part to be repaired. A microwave heating device is used to form a strong magnetic field distribution around the interwoven graphite powder and the glass fiber, thereby generating induction heat, uniformly heating the fluid glue, and the dimethylformamide solvent evaporates quickly. The curing agent reacts with the epoxy resin, thereby achieving rapid curing of the fluid glue.

[0094] Although dimethylformamide has good solubility, it is toxic and irritating to a certain extent. When using it, make sure to wear appropriate protective equipment and operate in a well-ventilated environment.

[0095] Embodiment 4:

[0096] 110 parts of epoxy resin, 1.2 parts of silane coupling agent KH560, 40 parts of boron nitride thermal conductive filler, 7 parts of low-viscosity polyamide curing agent, 30 parts of mixed solvent (xylene and ethyl acetate 1:1) and 1 glass fiber mesh are also doped.

[0097] Adding curing agent and solvent: In the reactor, slowly add low-viscosity polyamide curing agent under negative pressure, and continue stirring until it is completely dissolved to avoid bubbles. Use a two-stage stirring method, first stir at a low speed to evenly disperse the filler, and then stir at a high speed to promote the full reaction of the curing agent and the resin. Subsequently, add xylene and ethyl acetate solvents to adjust the viscosity, and strictly control the volatilization of harmful gases during the whole process.

[0098] During the stirring process, the electromagnetic induction heating furnace uses electromagnetic induction heating of the glass fiber mesh to make the induction heat more evenly distributed inside the fluid glue, avoiding the problem of local overheating and local flash evaporation. At the same time, the staged heating power control is set according to the temperature, which ensures the heating efficiency and avoids flash evaporation under the premise of avoiding flash evaporation.

[0099] The treated fluid glue is transferred to another reaction kettle, a cross-linking agent is added thereto, and after being stirred evenly, vacuum treatment is performed again to remove gas impurities that may be generated during the reaction.

[0100] Coating and curing: The prepared repair glue is evenly coated on the surface of the insulating part to be repaired. A microwave heating device is used to form a strong magnetic field distribution around the interwoven graphite powder bonded to the glass fiber, thereby generating induction heat, uniformly heating the fluid glue, and the 1:1 mixed solvent of xylene and ethyl acetate evaporates quickly, and the curing agent reacts with the epoxy resin, thereby achieving rapid curing of the fluid glue.

[0101] The full reaction of the curing agent and the resin under high-speed stirring can effectively improve the strength of the curing accelerated insulation repair adhesive.

[0102] Although xylene and ethyl acetate have strong dissolving ability, they are also toxic and irritating to a certain extent. When using them, make sure to wear appropriate protective equipment and operate in a well-ventilated environment.

[0103] Embodiment 5:

[0104] 100 parts of epoxy resin, 1 part of environmentally friendly silane coupling agent γ-glycidyloxypropyltrimethoxysilane, 50 parts of composite inorganic filler (aluminum hydroxide and magnesium oxide mixed in a ratio of 1:1), 3 parts of bio-based curing agent (such as phytic acid), and the water-based solvent system is also doped with 1 glass fiber mesh.

[0105] Adding curing agent and solvent: In the reactor, slowly add the bio-based curing agent under negative pressure. The bio-based curing agent has a polyhydroxy structure and can react chemically with materials such as epoxy resin to form a stable curing network. Continue stirring until it is completely dissolved to avoid bubbles. Then, add a water-based solvent to adjust the viscosity.

[0106] Temperature control: During the stirring process, the electromagnetic induction heating furnace uses electromagnetic induction heating of the glass fiber mesh to make the induction heat more evenly distributed inside the fluid glue, avoiding the problem of local overheating and local flash evaporation. At the same time, the staged heating power control is set according to the temperature, which ensures the heating efficiency and avoids flash evaporation under the premise of avoiding flash evaporation.

[0107] The treated fluid glue is transferred to another reaction kettle, a cross-linking agent is added thereto, and after being stirred evenly, vacuum treatment is performed again to remove gas impurities that may be generated during the reaction.

[0108] Coating and curing: The prepared repair glue is evenly coated on the surface of the insulation to be repaired. A microwave heating device is used to form a strong magnetic field distribution around the interwoven graphite powder and the glass fiber, thereby generating induction heat and evenly heating the fluid glue. The water-based solvent can evaporate quickly, and then the curing agent reacts with the epoxy resin to achieve rapid curing.

[0109] The use of water-based solvents can reduce VOC emissions and the impact on the environment. Bio-based curing agents are more environmentally friendly and suitable for places with high environmental protection requirements.

[0110] Different formulas and preparation processes of the rapid insulation repair adhesive of the present invention are demonstrated. These examples not only verify the feasibility and effectiveness of the present invention, but also demonstrate its adaptability and flexibility in different application scenarios. The rapid insulation repair adhesive of the present invention will provide a corrosion-resistant, high-strength, easy-to-use repair adhesive that is resistant to moisture and salt spray corrosion for the insulation repair work of the power system.

[0111] Importantly, it should be noted that the construction and arrangement of the present application shown in a number of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible, for example, the size, scale, structure, shape and proportion of various elements, and parameter values ​​such as temperature, pressure, etc., mounting arrangements, use of materials, color, directional changes, etc., without substantially departing from the novel angles and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of the execution function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other substitutions, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0112] Furthermore, in order to provide a concise description of exemplary embodiments, all features of the actual embodiment may not be described, namely those features that are not relevant to the best mode presently contemplated for carrying out the invention or those features that are not relevant to implementing the invention.

[0113] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, the development effort will be a routine task of design, fabrication, and production without undue experimentation.

[0114] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A production process for a repair adhesive that is resistant to moisture and salt spray corrosion, characterized in that: The following steps are involved: Step (1) mixing epoxy resin, silane coupling agent, inorganic filler, and glass fiber mesh in a doped state in a reactor, and evacuating the reactor before mixing; The silane coupling agent includes γ-aminopropyltriethoxysilane, γ-vinyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane; In terms of weight percentage, epoxy resin 50%-58%, silane coupling agent 0.7%-0.8%, inorganic filler 22%-28%; The glass fiber mesh comprises a mesh body and expanded glass fibers; The net body is woven with warp and weft; Both the warp and weft threads are made of fiberglass; The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers; Step (2) adding a curing agent to the reaction kettle and stirring sufficiently to allow the components to react sufficiently, wherein the curing agent is 0.02% to 0.03% by weight; Step (3) adding solvent to the reaction kettle to adjust the viscosity of the coating, in terms of weight percentage, the solvent is 1%-1.5%, and the materials in the reaction kettle are mixed to form a fluid glue; Step (4) transferring the stirred and mixed fluid glue to another reaction kettle, adding a crosslinking agent thereto, stirring evenly, and then performing a vacuum treatment again to remove gas impurities generated during the reaction; In terms of weight percentage, the cross-linking agent is 0.7%-1%; Step (5) uniformly coating the prepared coating on the surface of the insulating part to be repaired; Step (6) solidifies under heating conditions to form a dense insulating protective layer.

2. The production process of the repair glue for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: In the glass fiber mesh, the diameter of the glass fibers is 6.2-9.5 μm; The area of ​​the mesh is 0.55-2.5mm 2 , mesh area is 0.01-0.18mm 2 ; The length of the expanded glass fiber is 0.45-1.95mm; In terms of volume, there are 3-6 glass fiber meshes per cubic centimeter.

3. The production process of the repair glue for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: The inorganic filler includes aluminum oxide, silicon oxide, hollow glass microspheres and boron nitride The inorganic filler also includes a 1:1 mixture of aluminum hydroxide and magnesium oxide.

4. The production process of the repair adhesive for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: In step (2), the curing agent is added under negative pressure and stirred until dissolved to reduce the generation of bubbles; A two-stage stirring method is used, first stirring at a low speed to evenly disperse the filler, and then stirring at a high speed to promote the full reaction of the curing agent and the resin; The curing agent includes a polyamide resin curing agent, a polyamide-amine type curing agent and a bio-based curing agent.

5. The production process of the repair adhesive for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: The solvents include a water-based solvent, a 1:1 mixed solvent of xylene and ethyl acetate, a dimethylformamide solvent and a butyl acetate solvent.

6. The production process of the repair adhesive for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: When the fluid adhesive in another reaction kettle is stirred in step (4), a protective gas is poured into the other reaction kettle. After the protective gas is poured in, stirring is continued to fully mix the protective gas and the fluid adhesive.

7. The production process of the repair adhesive for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: An electromagnetic induction heating furnace is also provided for heating the fluid glue in the reaction kettle; The electromagnetic induction heating furnace has an automatic temperature control system, and the automatic temperature control system has a microprocessor system; The soft magnetic powder on the glass fiber net has soft magnetic properties, which can introduce the magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties relatively uniformly heated; A temperature sensor is also provided in the reactor, and the temperature sensor is connected to the microprocessor system; The electromagnetic induction heating furnace is operated at high power below 80 degrees Celsius in the reactor; The electromagnetic induction heating furnace is operated at medium power when the temperature in the reactor is above 80 degrees Celsius, and the medium power is 50%-70% of the high power value; The electromagnetic induction heating furnace is operated at a low power level at a temperature above 150 degrees Celsius in the reactor, with the low power level being 20%-30% of the high power level.

8. The production process of the repair adhesive for preventing moisture and salt spray corrosion according to claim 1 is characterized in that: In step (1), the method for producing a glass fiber mesh, (1) When drawing the glass fiber used as one of the warp and weft threads, soft magnetic powder dust is sprayed onto the molten glass fiber through a nozzle in a molten state to adhere the soft magnetic powder powder, and the particle size of the soft magnetic powder is 0.05-0.20 μm; (2) When drawing the other type of glass fiber used as the warp or weft, soft magnetic powder is sprayed onto the molten glass fiber through a nozzle in a molten state, and then graphite powder is bonded to the molten glass fiber. The particles of the graphite powder are 6-10 μm.

9. The process for producing a repair adhesive resistant to moisture and salt spray corrosion according to claim 8, characterized in that: Step (6) the fluid glue is assisted in curing by an auxiliary curing device, the auxiliary curing device includes an electromagnet, an oscillating circuit is connected to the electromagnet to generate a magnetic field with periodic direction changes, and the electromagnet is close to the fluid glue coating position; The soft magnetic powder on the glass fiber can vibrate in an alternating magnetic field to expel the air in the fluid glue. The vibration also promotes the tightness of the glass fiber and the fluid glue. The glass fiber mesh has graphite powder mixed with the fluid glue to form a conductive fluid.

10. The process for producing a repair adhesive that is resistant to moisture and salt spray corrosion according to claim 9, characterized in that: Step (6) the auxiliary curing equipment includes a microwave heating device, and the fluid glue is heated and cured by the microwave heating device; Glass fiber bonded with soft magnetic powder guides the magnetic field generated by the microwave heating device into the deep of the fluid glue; In addition, the interwoven and bonded graphite powder forms a strong magnetic field distribution around the glass fiber, thereby generating induction heat.